Tracheal granular cell tumour presenting with throat discomfort. Issue 1 (7th November 2019) - Nakagawara, Kensuke; Sasaki, Mamoru; Morinaga, Shojiroh; Minematsu, Naoto
Abstract : Granular cell tumours (GCTs) are a rare form of neoplasm found throughout the body. Tracheobronchial involvement is less common. We describe a case of tracheal GCT in a 37‐year‐old Japanese woman presenting with throat discomfort. A tracheal tumour was found during laryngoscopy for undefined throat discomfort. Bronchoscopy demonstrated a white sub‐epithelial solitary nodule on the tracheal wall, and pathological examination of the biopsy samples confirmed GCT. No therapeutic procedures were performed, and the tumour is currently under strict observation. Throat discomfort is a rare presentation of tracheal tumours, but an early inspection using laryngoscopy and bronchoscopy may be helpful in determining an accurate diagnosis. Abstract : We report a rare case of tracheal granular cell tumours (GCT) presenting with throat discomfort as an initial symptom. While the symptom was atypical for a tracheal tumour, an early laryngoscopy and bronchoscopy led to the correct diagnosis.